New agroforestry network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The African Network for Agroforestry Education (ANAFE) has been set Up to strengthen the teaching of multidisciplinary approaches to land management in agroforestry in schools and training programmes. The network is managed by the Education...